ON TANABE KUNIO`S ARTICLE “FAMILIARIZING WITH THE ACHIEVEMENTS, LEARNING FROM OUR PIONEERS. VASILIY YEROSHENKO: STAYING IN JAPAN AND HIS FRIENDS - Julia V. Patlan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article written by the blind Masseur and Esperantist Mr. Tanabe Kunio and is translated into Russian in the year of the author’s 75th anniversary with his permission. The study, first published in 2013, is a modern evidence of V.J. Eroshenko’s activity and experience of staying in Japan namely what’s considered to be the most important for the blind. Like Vasily Eroshenko, Mr. Tanabe Kunio, who is a graduate of the Tokyo School for the Blind, is a masseur and Esperantist, so his experience is somewhat unique. The author’s attention is focused on what had been already achieved by the predecessors and, thus, could be repeated, and perhaps, improved. That’s why, the history development of the blind social movement in different countries is extremely significant for all modern blind people by following an example of the life achievements of their predecessors. This translation expands the theme of the years spent by Vasily Yeroshenko in Japan, initiated by Mrs. Isaki Michiko, a former teacher at the Tokyo School for the Blind, in her article “Eroshenko and the Tokyo Blind School”. However, it should not be viewed one-sidedly without taking into account the experience of the blind themselves. Fortunately, it was quite unique when sighted and blind researchers worked on the study of the archives of the Tokyo School for the Blind simultaneously and in a rather narrow circle. In such a cooperation, small groups of sighted and blind scholars were absolutely reasonable. Therefore, the blind scolars could bring together information from raised (Braille) manuscripts and publications that are unobtainable to sighted; and vice versa sighted ones gathered information from ordinary handwritten and printed sources inaccessible to the blind. It apeared that almost semultaneously studies of sighted and blind authors were written on the same historical material. This phenomenon is unique and gives us the opportunity to consider two articles as a kind of diptych, where one can see a number of nuances that would otherwise go unnoticed. The attention of the blind author Tanabe Kunio is attracted by Eroshenko’s activism, perseverance and mobility, as well as his ability to achieve goals, that is, the experience of the blind man surviving in extreme conditions, such as persecution, active participation in the socialist movement, arrests and repeated expulsions. Close attention also should be paid to the conclusion of the article – which is visually impaired or unsighted should not blindly imitate the sighted people, rejecting their own special needs and requirements. The extreme value and significance of V.J. Eroshenko as a blind activist for the blind people in Japan in the early 20th and in the first third of the 21st century remains the same – he acted precisely as a blind both among the blind and among the sighted. A tangible emphasis on the role of Christianity and its ideas in forming personal activism and a network of organizations supporting the blind in Japan should as well be highlighted in the proposed article. This subject was not for consideration for almost a century, however, lately it has become increasingly topical. The researchers of the International Research Group “Vasily Eroshenko and his time” are preparing an Internet conference “The Gospel and Eroshenko”, which will be held in the form of submitting and publishing the materials in 2020–2022, timed to the 130th jubilee from Eroshenko’s birth and the 70th death anniversary of the writer.